The Effect of Physical Activity on the Non-cognitive Ability of Adolescents - Jianchao Qin; Jiali Yao; Luyan Teng (Nicolaus Copernicus University in Toruń, 2023)
Based on the Big Five personality trait dimensions of non-cognitive ability measures, the CFPS 2020 database was used as the basis, and the self-answered questionnaires and messages that were under the age of 18 and had information on physical activity were selected as the study sample from the total sample of 28590 in this database, and the valid 1562 samples were used as the study subjects, and the corresponding options and answers were selected as the dependent variables related to the Big Five personality of responsibility, agreeableness, extraversion, and neuroticism. After constructing a model with logit regression and calculating the marginal effects, it was empirically demonstrated that increasing the frequency of physical exercise (frequency) had positive promotion or improvement effects on adolescents' sense of responsibility, agreeableness, extraversion, and neuroticism, with the frequency of physical exercise (frequency) in the past 12 months as the dependent variable, and the effects were different between urban and rural areas, age, and gender. There were differences between urban and rural areas, age, and gender.